Impact of software team composition methodology on the personality preferences of Malaysian students - Gilal, A.R. (Institute of Electrical and Electronics Engineers Inc., 2016)
Inappropriate team composition is one of the important factors that impact the overall results of software development. Software development integrates the technical part of work with social norms. Many studies have been carried out in this domain to provide effective solution for the mentioned problem. But, the ambiguity of the problem exists in the team models and methodologies where different researchers accentuate on different individual types of personality for an effective role in the teamwork. Therefore, this study intended to measure the differences in the personality preferences after applying the proposed methodologies for software development team composition. For that purpose, this study used RAMSET (Role Assignment Methodology for Software Engineering Teams) methodology to measure the impact on personality preferences of Malaysian students. In the study experiment, six teams followed the RAMSET steps (called Group RAMSET or GR) and six teams did not follow (called Group Freestyle or GF). Based on the results, one impression can be made that the personality preferences affect the overall project success. Therefore, it is important to find the effective personality preferences for software development roles to incorporate within the models and methodologies. Â© 2016 IEEE.